Cardiovascular complications of cirrhosis. Issue 999 (24th February 2009) - Møller, S; Henriksen, J H
Abstract : Cardiovascular complications of cirrhosis include cardiac dysfunction and abnormalities in the central, splanchnic and peripheral circulation, and haemodynamic changes caused by humoral and nervous dysregulation. Cirrhotic cardiomyopathy implies systolic and diastolic dysfunction and electrophysiological abnormalities, an entity that is different from alcoholic heart muscle disease. Being clinically latent, cirrhotic cardiomyopathy can be unmasked by physical or pharmacological strain. Consequently, caution should be exercised in the case of stressful procedures, such as large volume paracentesis without adequate plasma volume expansion, transjugular intrahepatic portosystemic shunt (TIPS) insertion, peritoneovenous shunting and surgery. Cardiac failure is an important cause of mortality after liver transplantation, but improved liver function has also been shown to reverse the cardiac abnormalities. No specific treatment can be recommended, and cardiac failure should be treated as in non-cirrhotic patients with sodium restriction, diuretics, and oxygen therapy when necessary. Special care should be taken with the use of ACE inhibitors and angiotensin antagonists in these patients. The clinical significance of cardiovascular complications and cirrhotic cardiomyopathy is an important topic for future research, and the initiation of new randomised studies of potential treatments for these complications is needed.